Small carbon stocks in sediments of Baltic Sea eelgrass meadows - Billman, Maja; Santos, Isaac R.; Jahnke, Marlene (Frontiers in Marine Science, 2023)
Seagrass meadows act as an effective carbon sink and store carbon in the sediments for substantial periods of time. The drivers of carbon sequestration are complex, and global and regional estimates of carbon stocks have large uncertainties. Here, we report new carbon stock estimates from 14 sites along the Swedish coast and compile existing literature to estimate the magnitude of carbon stocks of Zostera marina (eelgrass) meadows in the Baltic Sea. Eelgrass meadows in the Baltic Sea have considerably lower carbon content and lower stocks (0.25 ± 0.21% DW, 635 ± 321 g C m-2) than in the Kattegat-Skagerrak region (3.25 ± 2.78% DW, 3457 ± 3382 g C m-2) and the average for temperate regions in general (1.4 ± 0.4% DW, 2721 ± 989 g C m-2). Unfavorable growing conditions for eelgrass in the Baltic Sea often lead to meadows occurring in areas of high hydrodynamics, preventing significant carbon accumulation. Stable isotopes revealed that the dominating source of organic carbon in the meadows was planktonic, further highlighting that Baltic Sea eelgrass meadows are not major carbon reservoirs in comparison to unvegetated sediments and other seagrass areas. The results also highlight that environmental conditions drive intraspecific variation of carbon sequestration on large spatial scales. Overall, the carbon stocks and sequestration potential in eelgrass meadows of the Baltic Sea are small compared to other temperate regions.